2017
DOI: 10.4049/jimmunol.1601705
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulation of miR-200a-3p, Targeting CtBP2 Complex, Is Involved in the Hypoproduction of IL-2 in Systemic Lupus Erythematosus–Derived T Cells

Abstract: Systemic lupus erythematosus (SLE) damages multiple organs by producing various autoantibodies. In this study, we report that decreased microRNA (miR)-200a-3p causes IL-2 hypoproduction through zinc finger E-box binding homeobox (ZEB)1 and C-terminal binding protein 2 (CtBP2) in a lupus-prone mouse. First, we performed RNA sequencing to identify candidate microRNAs and mRNAs involved in the pathogenesis of SLE. We found that miR-200a-3p was significantly downregulated, whereas its putative targets, ZEB2 and Ct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…SRSF1 levels are decreased in T cells from SLE patients, and overexpression of SRSF1 into SLE T cells, rescues IL-2 production ( 34 ). It was demonstrated that increased expression of miR-200a-3p is associated with the decreased production of IL-2 through zinc finger E-box binding homeobox–C-terminal binding protein 2 in MRL/lpr mice ( 216 ).…”
Section: Cytokine Signalingmentioning
confidence: 99%
“…SRSF1 levels are decreased in T cells from SLE patients, and overexpression of SRSF1 into SLE T cells, rescues IL-2 production ( 34 ). It was demonstrated that increased expression of miR-200a-3p is associated with the decreased production of IL-2 through zinc finger E-box binding homeobox–C-terminal binding protein 2 in MRL/lpr mice ( 216 ).…”
Section: Cytokine Signalingmentioning
confidence: 99%
“…The zinc finger E-box binding homeobox 1 gene, ZEB1, P SKAT.corr < 1.00E-03 and P burden.test.corr < 1.00E-03, OR enrich = 2.03 and CI 95%.enrich = (1.35, 3.05), acts as a transcriptional repressor inhibiting interleukin-2 (IL-2) gene expression. Note that IL-2 plays a critical role in immune tolerance, and insufficient IL-2 production upon stimulation has been recognized in SLE pathogenesis, particularly it has been described a new epigenetic pathway in the control of IL-2 production in SLE whereby low levels of miR-200a-3p accumulate the binding of the ZEB1-CtBP2 complex to the IL-2 promoter and suppresses IL-2 production (50). The role of CCR3 [P SKAT.corr = 0.00838 and P burden.test.corr < 1.00E-03, OR burden.test = 3.74 and CI 95%.burden.test = (1.74, 8.02)] in inflammation is widely known (OMIM * 601268).…”
Section: Discussionmentioning
confidence: 99%
“…Illumina TruSeq ChIP Sample Prep Kit was used for the construction of sequencing libraries, and they were subjected to sequencing using Illumina HiSeq. The previously published mRNA sequencing data 10 appeared in Gene Expression Omnibus (https://www.ncbi.nlm.nih.gov/geo/) under the accession number GSE87219 was analyzed with Cuffdiff program, and integrated with genome wide DNA methylation profiling data (GSE102421). In brief, significant methylation peaks in B6 and MRL mice were identified with model-based analysis of ChIP-Seq (MACS 1.4.2) using parameters bandwidth = 300, mfold = 10,30, and gzise = 1870000000 50 , mapped to genome, differentially methylated regions (DRMs) between B6 and MRL mice identified, and duplicate reads removed.…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that hypomethylation of a CpG within cAMP response element (CRE) motif links to increased expression of PP2Acα in T cells derived from the patients with SLE 9 . We also performed global miRNA and mRNA profiling in CD4+ T cells purified from spleen of MRL/lpr lupus-prone mice (MRL) and compared with the C57BL/6 (B6) and isolated miR-200a-3p, which is involved in the hypoproduction of IL-2 in T cells by targeting CtBP2 complex 10 . To identify the putative methylation-sensitive genes involved in the pathogenesis of SLE, we performed the integration analysis of genome-wide DNA methylation and global mRNA profiling in CD4+ T cells purified from spleen of MRL and compared with B6 mice.…”
Section: Introductionmentioning
confidence: 99%